The Price to Pay: An Empirical Analysis of the Relationship Between Hexagon Fraud and Financial Performance of East Javanese Banks - Susilowati, Endang (Proceedings of International Conference of Graduate School on Sustainability, 2025)
This study aims to analyze the relationship between Hexagon Fraud and financial performance in East Javanese banks, with Corporate Governance as a moderating variable. This study uses path analysis with a population of 437 banks. The sample size, determined using the Slovin formula, is 209 banks. The results indicate that Hexagon Fraud significantly affects financial performance, and Corporate Governance substantially moderates the relationship between Hexagon Fraud and financial performance. Improved Corporate Governance can weaken the negative impact of Hexagon Fraud on banks’ financial performance, highlighting the importance of transparent and accountable governance practices for banks.